Intimate partner violence and women's economic insecurity - Resko, Stella M., 1978- (Criminal justice (LFB Scholarly Publishing LLC), 2010)
Resko examines the relationship between women's economic wellbeing and intimate partner violence. Using data from the Fragile Families Survey, she examines hypotheses shaped by stress theory and social exchange theory and investigates racial and ethnic differences in these models. Her results support the notion that improving women's economic position can reduce intimate partner violence. Little evidence supported the backlash hypothesis, but in some situations men's poor performance in the labor force may be associated with an increased abuse. The strength of these results, however, differs a.